(untitled) (Eurasian Research Bulletin, 2023)
Surrogate motherhood is the process of carrying and giving birth to a child by a woman, that is, a surrogate mother for the further transfer of the child to potential parents. In many cases, the genetic material of a man and a woman for the formation of an embryo is provided by a person carrying a child. In some cases, a surrogate mother can also be a genetic mother (negotiated individually). Surrogacy is resorted to when pregnancy and childbirth are undesirable or impossible from a medical point of view, when the risks of pregnancy are too dangerous for the mother, or when a single man wants to have a child.